Hepatitis B virus antigens in primary hepatic carcinoma: immunofluorescent techniques on fixed liver tissue. Issue 12 (December 1978) - Trevisan, A; Realdi, G; Losi, C; Ninfo, V; Rugge, M; Rampinelli, L
Abstract : The presence of hepatitis B surface (HBsAg) and core (HBcAg) antigens was investigated by immunofluorescence in specimens of liver tissue obtained at necrospy in 107 patients with primary hepatic carcinoma. HBsAg was detected in the cytoplasm of liver cells in 16 cases, and in eight of them the antigen was also found in malignant cells. HBcAg, which was present in the nuclei of liver cells in eight cases, was detected in the nuclei of tumour cells in six of these and also in two other cases showing HBsAg, but not HBcAg, in the nonneoplastic tissue. Although most of the primary hepatic carcinomas studied were associated with cirrhotic changes in the non-neoplastic tissue, HBsAg and HBcAg were also detected in the absence of underlying cirrhosis. Hepatitis B virus markers were demonstrated in non-neoplastic tissue, mainly in patients with a well-differentiated carcinoma, and only in these cases were they found also in the neoplastic tissue. These results show that hepatitis B virus antigens, including HBcAg, can be detected in the neoplastic cells of well-differentiated carcinoma of the liver. Although these cells could have been infected after the malignant transformation, a direct oncogenic role of the virus cannot be excluded.